UPM Vice-Chancellor Fellowship Awards 2011 - The Star, (2012)
• Mathematical expert in numerical analysis and parallel programming .. • Awarded Excellent Service and Excellent Teaching at the faculty level, and also received the Choice Lecturer Award in the Faculty of Science. • Implemented innovative practices in teaching and learning activities to increase students' intellectual development and thinking skills.